Exploiting plant growth promoting Trichoderma for lentil wilt management - JAVERIA, SHAILY; KUMAR, ATUL; KHARKWAL, AMIT C; VARMA, AJIT; SHARMA, PRATIBHA (The Indian Journal of Agricultural Sciences, 2020)
Fusarium wilt caused by Fusarium oxysporum f. sp. lentis (Fol) has been considered as destructive seed and soil-borne disease of lentil which causes severe yield loss every year. For its biological control, twenty isolates of Trichoderma spp. were tested against thirty Fol isolates using dual culture technique. Out of twenty Trichoderma isolates, seven isolates (5593, ThL-1, ThL-4, TaL- 2, TaL- 4, ThaL-3 and TvL-6) showed maximum percent inhibition of radial growth against pathogens between 82.4% to 78.0% as compared to the rest of Trichoderma isolates. As far as molecular identification is concerned the effective six isolates after dual culture assay and highly virulent Fol isolate were molecularly identified by using ITS primers (ITS 1 and ITS 4) and remaining one isolate was taken from ITCC which was already identified as T. harzianum (5593). Seven efficient isolates of Trichoderma were used to evaluate volatile and non- volatile assay against Fol (NFLRJ-3). Isolates, 5593 and ThL-4 showed significant growth inhibition against Fol at 48 hours of incubation in both the assays as compared to the rest Trichoderma isolates. In volatile organic compound (VOC) assay ThL-4 showed highest number of seed germination and showed good seed health condition. Out of seven selected isolates of Trichoderma, all isolates were found effective to control disease and stimulated plant growth promotion activity of lentil (2017-2019). Therefore, these isolates can be utilized to formulate bio-fungicides which is the need of the hour as far as disease management is concerned.